2018
DOI: 10.1097/fpc.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analyses identifies novel taxane-induced peripheral neuropathy-associated loci

Abstract: The genetic variants associated with ≥grade 3 TIPN are hypothesized to have biochemical functions and reside in and near genes involved in diabetes and diabetic neuropathy. This finding is consistent with results from CALGB 40101 pathway analyses. Larger homogeneous trials with similar dosing and criteria for defining neuropathy are needed to properly assess the relationship of genomics with the neuropathy spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…TUBB2A variants were demonstrated to increase transcription rate and protect cells from paclitaxel toxicity . Similarly, SNPs in TUBB2A were identified in subsequent studies, but not in all reports …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…TUBB2A variants were demonstrated to increase transcription rate and protect cells from paclitaxel toxicity . Similarly, SNPs in TUBB2A were identified in subsequent studies, but not in all reports …”
Section: Introductionmentioning
confidence: 96%
“…Another study identified SNPs in CMT gene SBF2 as linked with severe TIPN in an African‐American patient cohort . Similarly, genes associated with diabetic neuropathy were found to be potentially linked to TIPN, including NXN . These results suggest common genetic pathways may contribute to taxane‐neurotoxicity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research has attempted to discover genetic predictors of paclitaxel‐induced PN or replicate previous findings. These important discoveries need to be fully validated to establish clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies exploring these associations mostly utilized a case–control approach with the endpoint of occurrence of PN. More recent studies have explored PN susceptibility by accounting for the cumulative dose at PN occurrence. Within these studies, variants in genes encoding ephrin ( EPHA) receptors from the receptor tyrosine kinase family, which have a role in neuronal development, have been observed to increase risk of paclitaxel‐induced PN (i.e.…”
Section: Introductionmentioning
confidence: 99%